(untitled) (Pedagogy of Higher and Secondary Education, 2021)
This atricle is devoted to the problem of formation of the skills and habits of self-control of the teachers. The essence of the prychological process of self-control as the science conception is examined. The conditions of formation of the skills and hubits of self-control of the teachers are defined.